Representasi Nilai Toleransi Antar Umat Beragama Dalam Film â€œMy Name Is Khanâ€ Karya Karan Johar (Analisis Semiotika Charles Sanders Pierce) - Ariqqa, Ariqqa; Sikumbang, Ahmad Tamrin; Harahap, Suheri (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the representation of the value of inter-religious tolerance in the film My Name Is Khan. The method used in this study is a semiotic analysis method that is descriptive. Where in this study using semiotic analysis from Charles Sanders Pierce. The object of this study is every scene that contains the value of tolerance between religious people.The results of this study show that the film